Phytochemical composition, mineral content and antioxidant activities of the methanol extract of Curcuma longa and Viscum album - Nwozo, Sarah Onyenibe; Effiong, Magdalene Eno (Journal of Food and Pharmaceutical Sciences, 2019)
The medicinal value of plants have assumed a more important dimension in the past few decades owing largely to the discovery that extracts from plants contain not only minerals and primary metabolites but also a diverse array of secondary metabolites with antioxidant potentials. However, there is dearth of knowledge on the medicinal uses and nutritional benefits of Curcuma longa and Viscum album. This study was designed to focus on the phytochemical and mineral composition in addition to the antioxidant activities of the methanol extracts of C. longa and V. album. Results indicated that the micro and macro mineral analysis exhibited significant presence of Fe, Zn, Mn, Ca and Mg while Cd, Pb, Ni and Cr were present in minute quantities. Phytochemical screening unravelled the presence of alkaloids, cardiac glycosides, steroids, phenols, tannins, saponins and flavonoids that were also proved by the quantitative analysis. There was a high correlation between the flavonoid content and antioxidant activities of the plant extracts. The antioxidant activities of the extracts were found to be concentration dependent. The results suggest that both plant extracts have good medicinal potentials and can serves as good sources of macro minerals.